The single-cell expression profile of transposable elements and transcription factors in human early biparental and uniparental embryonic development - Li, Conghui; Zhang, Yue; Leng, Lizhi; Pan, Xiaoguang; Zhao, Depeng; Li, Xuemei; Huang, Jinrong; Bolund, Lars; Lin, Ge; Luo, Yonglun; Xu, Fengping (Frontiers in Cell and Developmental Biology, 2022)
Transposable elements (TEs) and transcription factors (TFs) are involved in the precise regulation of gene expression during the preimplantation stage. Activation of TEs is a key event for mammalian embryonic genome activation and preimplantation early embryonic development. TFs are involved in the regulation of drastic changes in gene expression patterns, but an inventory of the interplay between TEs and TFs during normal/abnormal human embryonic development is still lacking. Here we used single-cell RNA sequencing data generated from biparental and uniparental embryos to perform an integrative analysis of TE and TF expression. Our results showed that endogenous retroviruses (ERVs) are mainly expressed during the minor embryonic genome activation (EGA) process of early embryos, while Alu is gradually expressed in the middle and later stages. Some important ERVs (e.g., LTR5_Hs, MLT2A1) and Alu TEs are expressed at significantly lower levels in androgenic embryos. Integrative analysis revealed that the expression of the transcription factors CTCF and POU5F1 is correlated with the differential expression of ERV TEs. Comparative coexpression network analysis further showed distinct expression levels of important TFs (e.g., LEUTX and ZSCAN5A) in dizygotic embryos vs. parthenogenetic and androgenic embryos. This systematic investigation of TE and TF expression in human early embryonic development by single-cell RNA sequencing provides valuable insights into mammalian embryonic development.